Coagulation screening tests in high risk neonates: a prospective cohort study. Issue 10 (October 1992) - Schmidt, B K; Vegh, P; Andrew, M; Johnston, M
Abstract : Forty seven infants in a prospective cohort of 170 high risk neonates without signs of overt bleeding had abnormal coagulation screening tests within 36 hours of birth. Early thrombocytopenia was a better predictor of prolonged prothrombin times and hypofibrinogenemia than very low birth weight, fetal growth retardation, or poor five minute Apgar scores.